Однонуклеотидный и инсерционно-делеционный полиморфизм гена FLG человека при кожных заболеваниях - Зуева, М.И.; Парфёнова, Д.О.; Атраментова, Л.А. (Фактори експериментальної еволюції організмів, 2013)
Aims. Mutations in FLG-2282del4 and R501X associated with the third exon variously relate to skin diseases. Methods. The detection of mutations was performed by PCR-RFLP. Results. The FLG mutation frequency in the Slavic population of the Kharkov region is рR501X = 0,010, р2282del4 = 0,005. Inheritance of FLG 2282del4 deletion increases probability of atopic dermatitis and eczema by ten times. This deletion can be considered as a marker of the appropriate genetic predisposition and used in predictive medicine. The sensitivity is 13–23 % and the specificity is 99 %. Prognostic significance of a positive result is 86–92 %, of negative result is 70–73 %. Conclusions. FLG-2282del4 mutation increases the risk of allergic dermatitis and homozygous individuals are exposed to particularly severe course of the disease. Carrier testing this deletion is useful when predicting an individual's genetic predisposition to allergic.